Holocene coastal evolution and environmental changes in the lower Río Guadiaro valley, with particular focus on the Bronze to Iron Age harbour 'Montilla' of Los Castillejos de Alcorrín (Málaga, Andalusia, Spain). Issue 2 (9th November 2022) - May, Simon Matthias; Brückner, Helmut; Norpoth, Maike; Pint, Anna; Wolf, Dennis; Brill, Dominik; Martín, César León; Stika, Hans‐Peter; Padilla, José Suárez; Moret, Pierre; Marzoli, Dirce
Abstract: Phoenicians were the first to systematically develop the area surrounding the Strait of Gibraltar at the end of the 9th century B.C. Following pioneering studies in the Río Guadiaro estuary (Málaga/Cádiz) in the 1980s, a German‐Spanish cooperation project focussed on the role of indigenous people in the Phoenician colonisation trading networks at Los Castillejos de Alcorrín (Manilva, Málaga), one of the most important Early Iron Age settlements in southwestern Iberia. In the recent past, combined with systematic archaeological surveys, geoarchaeological research embedded in the interdisciplinary project 'Archeostraits' aimed at (i) deciphering palaeoenvironmental and coastal changes in the surroundings of Los Castillejos de Alcorrín throughout the mid‐ to late Holocene; (ii) constraining palaeoenvironmental conditions during early Phoenician colonisation; and (iii) better understanding human–environment interactions during the Final Bronze and Early Iron Age (i.e., end of 9th and 8th centuries B.C.). Coring transects along the Río Guadiaro allowed for differentiating successive palaeoenvironments and for establishing a chrono‐stratigraphy for the Holocene sedimentary infill of the valley. Based on these results, the deposition of shallow marine sands, overlying deltaic deposits of alternating sand and mud, and the subsequent development of lagoonal conditions in the lower Guadiaro valley took place before the Phoenicians established the first settlements along the coast.